Altered glutamate–glutamine and amide proton transfer-weighted values in the hippocampus of patients with amnestic mild cognitive impairment: A novel combined imaging diagnostic marker - Chen, Xin; Gong, Tao; Chen, Tong; Xu, Changyuan; Li, Yuchao; Song, Qingxu; Lin, Liangjie; Oeltzschner, Georg; Edden, Richard A. E.; Xia, Zhangyong; Wang, Guangbin (Frontiers in Neuroscience, 2023)
Background and Purpose: Amnestic mild cognitive impairment (aMCI) is considered as a prodromal stage of Alzheimer's disease (AD). Growing evidence supports the hypothesis that unbalanced excitatory/inhibitory (glutamate and gamma-aminobutyric acid) neurotransmitters and consequent abnormal protein deposition in hippocampus contribute to the pathological process of MCI and AD, especially in the hippocampus. In this study, we aim to quantify hippocampal glutamate-glutamine (Glx) and gamma-aminobutyric acid (GABA）levels as well as amide proton transfer-weighted (APTw) signals of aMCI patients, and further to investigate the combined diagnostic performance of these metabolites. Methods: Twenty aMCI patients and 20 age- and gender-matched healthy controls (HCs) underwent MEGA Point Resolved Spectroscopy (MEGA-PRESS) and APTw MR imaging at 3 T prospectively. GABA+, Glx and APTw signals were measured in the right hippocampus. The GABA+ levels, Glx levels, Glx/GABA+ ratios and APTw values were compared between the aMCI and HC groups using Mann–Whitney U test. Receiver operating characteristic (ROC) curve analysis was used to evaluate MEGA-PRESS and APTw parameters' diagnostic performance. Results: Glx levels were significantly lower in right hippocampus of patients with aMCI compared to HCs (7.02 ± 1.41 i.u. vs. 5.81 ± 1.33 i.u., P=0.018). No significant changes of GABA+ levels were observed in aMCI patients (HCs vs. aMCI: 2.54 ± 0.28 i.u. vs. 2.47 ± 0.36 i.u., P=0.620). In addition, Glx/GABA+ ratios between the two groups (HCs vs. aMCI: 2.79±0.60 vs. 2.37 ± 0.55, P=0.035) were significantly different. Compared with HCs, aMCI patients showed higher APTw values in the right hippocampus (1.26%±0.28 vs. 0.99±0.26%, P=0.006). ROC curve analysis showed the under the curve (AUC) of Glx and APTw values for diagnosing aMCI was 0.72 and 0.75 respectively, whilst the AUC value when combination of the two parameters increased to 0.86. Conclusion Patients with aMCI exhibited decreased Glx level, Glx/GABA+ ratios and increased APTw values in right hippocampus. Combination of Glx levels and APTw values improved the diagnostic performance for aMCI, suggesting it as a promising combined imaging diagnostic marker.